Pengaruh Variasi Produk, Harga Dan Lokasi Terhadap Keputusan Pembelian Di TNA Collection Nganjuk - Ifa Sholihatin; Miftahul Munir; Agung Pambudi Mahaputra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The purpose of this study is to determine the influence of product variations, prices and locations on purchasing decisions at TNA Collection Nganjuk. The existence of various product variations, prices that are in accordance with the ability of consumer purchasing power and the location right on the side of the highway indicate that it can improve purchasing decisions. This type of research is quantitative with a sample number of 95 people. Data collection using questionnaires with analysis techniques of validity test, reliability test, classical assumption test, multiple linear regression, t test, F test and coefficient of determination. The results showed that the product variation t test had a significant effect on purchasing decisions. Then price has a significant effect on purchasing decisions. And location has a significant influence on purchasing decisions. In the F test results, product variations, price, and location simultaneously affect purchasing decisions at TNA Collection Nganjuk.